Monitoring of the Physical and Chemical Properties of a Gasoline Engine Oil during Its Usage. (27th March 2012) - Rahimi, Behnam; Semnani, Abolfazl; Nezamzadeh-Ejhieh, Alireza; Shakoori Langeroodi, Hamid; Hakim Davood, Massoud
Abstract : Physicochemical properties of a mineral-based gasoline engine oil have been monitored at 0, 500, 1000, 2000, 3500, 6000, 8500, and 11500 kilometer of operation. Tracing has been performed by inductively coupled plasma and some other techniques. At each series of measurements, the concentrations of twenty four elements as well as physical properties such as: viscosity at 40 and 100°C; viscosity index; flash point; pour point; specific gravity; color; total acid and base numbers; water content have been determined. The results are indicative of the decreasing trend in concentration of additive elements and increasing in concentration for wear elements. Different trends have been observed for various physical properties. The possible reasons for variations in physical and chemical properties have been discussed.